Tren Topik Penelitian Strategi Usaha Mikro, Kecil, dan Menengah: Implementasi Analisis Bibliometrik - Sulaiman, Haryaman Justisia; Muhammad Zhafir Afif (Universitas Dr. Soetomo, 2024)
The Covid-19 pandemic has affected the economic cycle; three years after the pandemic, the effects are still being felt. One of the involved business actors, MSMEs, must adopt strategic policy measures to maintain their competitive advantage. Using a Systematic Literature Review (SLR) and co-word analysis in a bibliometric approach, this paper seeks to analyze the development trend of MSME strategy keyword topics for the period 2020-2023. The generation of trending topics allows using keywords for further research purposes and strategic insights.